UMA PROPOSTA DE MITIGAÇÃO DO RISCO ASSOCIADO AO PROCESSO DE AQUISIÇÃO DE UMA CADEIA DE SUPRIMENTOS: O ESTUDO DE CASO DE UMA ORGANIZAÇÃO PÚBLICA BRASILEIRA - Salvador, Marcos Vitor (2013)
The objective of this research is to identify the various types of risks associated with the procurement process, which integrates the supply chain organization of public focus of this dissertation, and present a proposal to mitigate these risks. From the perceived risks, the study aims to verify that they produce kinds of disturbances in the management of their supply chain, and through the use of concepts obtained through extensive review of the literature on risk management in supply chains, submit a proposal mitigation of the risks studied. For it to be achieved success in the purpose of this research, the main concepts featured Network Systematic Literature Review (SLNA), obtained through the construct prepared by Colicchia and Strozzi (2012) were used. From there it was possible, after occasional meetings with professionals working in the area of supplies, to identify the main risks associated with the procurement process of the supply chain, responsible for procurement and contracting of goods and services from the public agency studied.